Heterotrophic nitrifiers and aerobic denitrifiers in process of simultaneous nitrification and denitrification disposing NH4+-N wastewater - SU Jun-feng; MA Fang; GAO Shan-shan; WEI LI; LI Wei-guo (浙江大学学报. 农业与生命科学版, 2007)
Heterotrophic nitrifiers were screened from bio-ceramic reactor, and were characterized using sodium acetate and ammonium chloride as carbon and nitrogen sources. The results obtained were that COD removal rate reached over 45%, TN and NH4+-N removal rate reached over 60%, and also the nitrification function of producing NOx--N was well. After domesticating activated sludge to enrich aerobic denitrifiers, 5 aerobic denitrifiers (f1, f2, f3, f5, f7) were isolated from it, and the removal of TN were 90.4%, 91.2%,94.6%, 95.6%, 97% by these strains, respectively. The process of removing ammoniac nitrogen was done by setting the heterotrophic nitrifying bacteria and aerobic denitrifiers on the sequencing batch reactor (SBR). The PCR-DGGE profiles showed that shift of microbial diversity correspond to the effect of nitrate removal. During the SBR stable performance period, heterotrophic nitrobacteria wgy5, wgy21, aerobic denitrifiers d5 and Pseudomonas sp. were dominant bacteria in SBR.